New Insights Into the Epigenetic Regulation of Inflammatory Bowel Disease - Xu, Jing; Xu, Hao-ming; Yang, Mei-feng; Liang, Yu-jie; Peng, Quan-zhou; Zhang, Yuan; Tian, Cheng-mei; Wang, Li-sheng; Yao, Jun; Nie, Yu-qiang; Li, De-feng (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) is a chronic inflammatory disease of the colonic mucosa. Environmental factors, genetics, intestinal microbiota, and the immune system are all involved in the pathophysiology of IBD. Lately, accumulating evidence has shown that abnormal epigenetic changes in DNA methylation, histone markers, and non-coding RNA expression greatly contribute to the development of the entire disease. Epigenetics regulates many functions, such as maintaining the homeostasis of the intestinal epithelium and regulating the immune system of the immune cells. In the present study, we systematically summarized the latest advances in epigenetic modification of IBD and how epigenetics reveals new mechanisms of IBD. Our present review provided new insights into the pathophysiology of IBD. Moreover, exploring the patterns of DNA methylation and histone modification through epigenetics can not only be used as biomarkers of IBD but also as a new target for therapeutic intervention in IBD patients.